Finance and Development, December 1977. (Finance and Development; Finance and Development, 1977)
This paper discusses the launch of the Brandt Commission. The paper highlights that during the week of the Annual Meetings of the Board of Governors of the World Bank and the IMF in Washington, D.C. (September 26-30, 1977), Willy Brandt, former Chancellor of the Federal Republic of Germany, announced that he would head an independent commission that would identify 'ways of restructuring international relations that would command the widest possible support.' The Commission will have about 15 members, both from developed and developing countries.